Protracted Bacterial Bronchitis in Children: Natural History and Risk Factors for Bronchiectasis - Wurzel, Danielle F; Marchant, Julie M; Yerkovich, Stephanie T; Upham, John W; Petsky, Helen L; Smith-Vaughan, Heidi; Masters, Brent; Buntain, Helen; Chang, Anne B (Chest, 2016)
Protracted bacterial bronchitis (PBB) and bronchiectasis are distinct diagnostic entities that share common clinical and laboratory features. It is postulated, but remains unproved, that PBB precedes a diagnosis of bronchiectasis in a subgroup of children. In a cohort of children with PBB, our objectives were to (1) determine the medium-term risk of bronchiectasis and (2) identify risk factors for bronchiectasis and recurrent episodes of PBB. One hundred sixty-one children with PBB and 25 control subjects were prospectively recruited to this cohort study. A subset of 106 children was followed for 2 years. Flexible bronchoscopy, BAL, and basic immune function tests were performed. Chest CT was undertaken if clinical features were suggestive of bronchiectasis. Of 161 children with PBB (66% boys), 13 were diagnosed with bronchiectasis over the study period (8.1%). Almost one-half with PBB (43.5%) had recurrent episodes (> 3/y). Major risk factors for bronchiectasis included lower airway infection with Haemophilus influenzae (recovered in BAL fluid) (P = .013) and recurrent episodes of PBB (P = .003). H influenzae infection conferred a more than seven times higher risk of bronchiectasis (hazard ratio, 7.55; 95% CI, 1.66-34.28; P = .009) compared with no H influenzae infection. The majority of isolates (82%) were nontypeable H influenzae. No risk factors for recurrent PBB were identified. PBB is associated with a future diagnosis of bronchiectasis in a subgroup of children. Lower airway infection with H influenzae and recurrent PBB are significant predictors. Clinicians should be cognizant of the relationship between PBB and bronchiectasis, and appropriate follow-up measures should be taken in those with risk factors.